The muscle anabolic effect of protein ingestion during a hyperinsulinaemic euglycaemic clamp in middle‐aged women is not caused by leucine alone. (29th August 2018) - van Vliet, Stephan; Smith, Gordon I.; Porter, Lane; Ramaswamy, Raja; Reeds, Dominic N.; Okunade, Adewole L.; Yoshino, Jun; Klein, Samuel; Mittendorfer, Bettina
Abstract : Key points: It has been suggested that leucine is primarily responsible for the increase in muscle protein synthesis after protein ingestion because leucine uniquely activates the mTOR‐p70S6K signalling cascade. We compared the effects of ingesting protein or an amount of leucine equal to that in the protein during a hyperinsulinaemic‐euglycaemic clamp (to eliminate potential confounding as a result of differences in the insulinogenic effect of protein and leucine ingestion) on muscle anabolic signalling and protein turnover in 28 women. We found that protein, but not leucine, ingestion increased muscle p‐mTOR Ser2448 and p‐p70S6K Thr389, although only protein, and not leucine, ingestion decreased muscle p‐eIF2α Ser51 and increased muscle protein synthesis. Abstract: It has been suggested that leucine is primarily responsible for the increase in muscle protein synthesis (MPS) after protein ingestion because leucine uniquely activates the mTOR‐p70S6K signalling cascade. We tested this hypothesis by measuring muscle p‐mTOR Ser2448, p‐p70S6K Thr389 and p‐eIF2α Ser51, as well as protein turnover (by stable isotope labelled amino acid tracer infusion in conjunction with leg arteriovenous blood and muscle tissue sampling), in 28 women who consumed either 0.45 g protein kg −1 fat‐free mass (containing 0.0513 g leucine kg −1 fat‐free mass) or a control drink ( n  = 14) or 0.0513 g leucine kg −1 fat‐free mass or a control drink ( n  = 14) during a hyperinsulinaemic‐euglycaemic clamp procedure (HECP). Compared to basal conditions, the HECP alone (without protein or leucine ingestion) suppressed muscle protein breakdown by ∼20% and increased p‐mTOR Ser2448 and p‐p70S6K Thr389 by >50% (all P  < 0.05) but had no effect on p‐eIF2α Ser51 and MPS. Both protein and leucine ingestion further increased p‐mTOR Ser2448 and p‐p70S6K Thr389, although only protein, and not leucine, ingestion decreased (by ∼35%) p‐eIF2α Ser51 and increased (by ∼100%) MPS (all P  < 0.05). Accordingly, leg net protein balance changed from negative (loss) during basal conditions to equilibrium during the HECP alone and the HECP with concomitant leucine ingestion and to positive (gain) during the HECP with concomitant protein ingestion. These results provide new insights into the regulation of MPS by demonstrating that leucine and mTOR signalling alone are not responsible for the muscle anabolic effect of protein ingestion during physiological hyperinsulinaemia, most probably because they fail to signal to eIF2α to initiate translation and/or additional amino acids are needed to sustain translation. Key points: It has been suggested that leucine is primarily responsible for the increase in muscle protein synthesis after protein ingestion because leucine uniquely activates the mTOR‐p70S6K signalling cascade. We compared the effects of ingesting protein or an amount of leucine equal to that in the protein during a hyperinsulinaemic‐euglycaemic clamp (to eliminate potential confounding as a result of differences in the insulinogenic effect of protein and leucine ingestion) on muscle anabolic signalling and protein turnover in 28 women. We found that protein, but not leucine, ingestion increased muscle p‐mTOR Ser2448 and p‐p70S6K Thr389, although only protein, and not leucine, ingestion decreased muscle p‐eIF2α Ser51 and increased muscle protein synthesis.